2021
DOI: 10.1089/ars.2020.8168
|View full text |Cite
|
Sign up to set email alerts
|

Liver Sinusoidal Endothelial Cells at the Crossroad of Iron Overload and Liver Fibrosis

Abstract: Significance Liver fibrosis results from different etiologies and represents one of the most serious health issues worldwide. Fibrosis is the outcome of chronic insults on the liver and is associated with several factors, including abnormal iron metabolism. Recent AdvancesMultiple mechanisms underlying the pro-fibrogenic role of iron have been proposed. The pivotal role of Liver Sinusoidal Endothelial Cells (LSECs) in iron level regulation, as well as their morphological and molecular de-differentiation occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 123 publications
1
3
0
Order By: Relevance
“…The fenestration of liver sinusoidal endothelial cells (LSECs) is regarded as a dynamic structure that can be easily affected by nearby environment. [41][42][43] Similar to the sinusoidal defenestration change caused by iron overload, 31,44 our results showed a loss of fenestration in the iron overload groups. In particular, almost no fenestration was observed in the super-old iron-overloaded mice.…”
Section: Discussionsupporting
confidence: 69%
“…The fenestration of liver sinusoidal endothelial cells (LSECs) is regarded as a dynamic structure that can be easily affected by nearby environment. [41][42][43] Similar to the sinusoidal defenestration change caused by iron overload, 31,44 our results showed a loss of fenestration in the iron overload groups. In particular, almost no fenestration was observed in the super-old iron-overloaded mice.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have found that iron overload can lead to the atrophy and dysfunction of organs such as the liver, heart, muscles or brain ( 33 , 34 ). In the present study, iron accumulation in the pancreas may be associated with pancreatic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…29 30 Furthermore, dedifferentiated LSECs play a role in generating the inflammatory milieu and altering intrahepatic immunity, promoting fibrosis. 31 Fibrosis is considered a dynamic and reversible process termed fibrosis resolution/regression when the underlying causes are eliminated. Coculturing differentiated LSECs with activated HSCs and using an sGC activator to maintain LSEC differentiation can lead to the reversion of activated HSCs back to a quiescent state.…”
Section: Kupffer Cellsmentioning
confidence: 99%